2020
DOI: 10.1038/s41398-020-0752-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation meta-analysis in the brains of suicide completers

Abstract: Suicide is the second leading cause of death globally among young people representing a significant global health burden. Although the molecular correlates of suicide remains poorly understood, it has been hypothesised that epigenomic processes may play a role. The objective of this study was to identify suicide-associated DNA methylation changes in the human brain by utilising previously published and unpublished methylomic datasets. We analysed prefrontal cortex (PFC, n = 211) and cerebellum (CER, n = 114) D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 81 publications
0
35
0
Order By: Relevance
“…Using postmortem brain samples ( Pandey et al., 2019b ), observed overexpressed protein or mRNA of TLR2-4,6,10 in the prefrontal cortex of depressed suicide decedents. Recent genetic studies have supported involvement of immune-related pathways in suicide ( DiBlasi et al., 2020 ; Policicchio et al., 2020 ). Polygenic risk estimations are undergoing.…”
Section: Future Directionsmentioning
confidence: 99%
“…Using postmortem brain samples ( Pandey et al., 2019b ), observed overexpressed protein or mRNA of TLR2-4,6,10 in the prefrontal cortex of depressed suicide decedents. Recent genetic studies have supported involvement of immune-related pathways in suicide ( DiBlasi et al., 2020 ; Policicchio et al., 2020 ). Polygenic risk estimations are undergoing.…”
Section: Future Directionsmentioning
confidence: 99%
“…In the frontal cortex BDNF is also reduced but it seems to be the effect of gene inhibition based on its methylation. Considering the above knowledge and data from studies indicating both an increase in global DNA methylation [4] and the presence of hypomethylated regions at selected genetic loci in suicides [32,33], it seems justified and necessary to further investigate the role of MeCP2 in the context of mood disorders. HDAC2 increased in HP impaired special memory and synaptic plasticity [74] and with HDAC5 plays important role in MDD patients [75].…”
Section: Plos Onementioning
confidence: 99%
“…Interestingly, methylomic profiling of brain samples revealed differentially methylated regions (DMRs) in certain genetic loci (especially upstream of the PSORS1C3 gene) associated with suicidal depression. More detailed study of these samples indicated hypomethylated areas within these DMRs and discrete modules of co-methylated loci related with polygenic risk burden only for suicide attempt (not major depression) [32]. On this basis, Murphy et al (2020) conclude the existence of coordinated alterations in DNA methylation that are associated with SB [33].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations